Integrating Artificial Intelligence into Madrasah Learning: A Mixed-Methods Study of Intelligent Media Development and Implementation - Raehang; Muhammad Shaleh Assingkily; Mustapa Ahmad (Yayasan Zia Salsabila, 2025)
This study investigates the integration of Artificial Intelligence (AI)-assisted media in madrasah learning environments, addressing the limited availability of culturally and pedagogically responsive educational technologies in Islamic primary education. The research aims to develop and implement intelligent instructional media tailored to the cognitive, moral, and spiritual needs of madrasah students, while evaluating its impact on learning comprehension, reasoning, and communication. Employing a mixed-methods approach, this study combines qualitative data—analyzed using the latest NVivo software—from interviews, observations, and document analysis, with quantitative insights from user feedback and learning outcome measures. The results reveal that AI-integrated media significantly enhanced students’ conceptual understanding, verbal and non-verbal communication skills, and creative expression. Additionally, teachers reported reduced instructional burden and improved student engagement. The findings contribute to the emerging field of AI in education by proposing a culturally grounded framework for AI adoption in Islamic schooling. This study not only underscores the transformative potential of AI in promoting inclusive, meaningful learning experiences in madrasahs, but also calls for strategic teacher training, ethical design, and policy support to ensure sustainable and value-aligned implementation.